Optical and Electrochemical Properties of Co3O4/SiO2 Nanocomposite - Ali, Gomaa A. M.; Fouad, Osama A.; S. A., Makhlouf; M. M., Yusoff; K. F., Chong (Trans Tech Publications, Switzerland, 2016)
Co3O4/SiO2 nanocomposite was obtained via citrate-gel method. 22 nm in size Co3O4 particles in an amorphous SiO2 matrix were obtained. Co3O4:SiO2 wt. ratio was verified using EDX and found to be close to the 80 % nominal ratio. The UV-Vis measurements showed broad absorption bands at around 440 and 790 nm. The optical band gap values were 1.95 and 1.35 eV respectively, being close to those observed for pure Co3O4 nanoparticles. The electrochemical measurements in 5 M KOH solution were performed using a three-electrode type system. Co3O4/SiO2 nanocomposite exhibited high specific capacitance reaching 758 F g-1 at 2.5 mV s-1. Very small solution and electrode-electrolyte interfacial charge transfer resistances were obtained when impedance spectra were analysed.